Role of the tourism sector in the Iraqi economy - Ahmed, Younis Ali (2014)
Tourism has been a significant industry to the economy since the beginning of human civilization, and is becoming more vital in the future. Many countries all over the world continue to attract tourists to destinations in their respective countries since the late 20th century. Ample attention has been given to the role of tourism in the national economy and to the promotion of tourist activities in different areas. Due to the positive potential of tourism industry, Iraq supposed to take the opportunity and seriously involve itself in the industry. Iraq can be regarded as one of the greatest tourist sites in the world. Iraq can become an attractive destination for domestic and inbound tourism when investments are provided and ample attention is given to the development of the tourism industry. However, until today the attention that been given by Iraq to the tourism industry is still less as compared to the oil and gases industry. The importance of the oil and gas industry is undeniable however, provide an opportunity to expand the economic base is also important. Moreover, the development of tourism industry has been seen as a good potential to Iraq economy. Research on tourism demand and tourism growth in Iraq is also scarce. Most researchers and scholars have conducted research on strategic components of tourism in general or for a short period, and to the best knowledge of the researcher there is no current literature on tourism in Iraq that analyzes long-run and short-run relationships between tourism demand and its determinants. Therefore, this study provides a good analysis and its findings serve to fill the gaps in the literature on the role of tourism sector in the Iraqi economy. Due to the importance of tourism as an engine of economic growth and the lack of research in this field, research in the field of tourism has been carried out. Specifically, this study attempts to provide analysis that can fill the gap in the literature on the role of the tourism sector in the economy of Iraq. This study tries to analyze the role of the tourism sector in the Iraqi economy by providing an explanation of determinant variables in domestic tourism demand, inbound tourism demand, and economic growth. To achieve this goal, ARDL method, with three major models, namely, domestic tourism demand, inbound tourism demand and economic growth model have been applied. The main advantage of ARDL modeling is that it can estimate the long-run and short-run relationships in the tourism demand and economic growth models. Moreover, the error correction term (ECT) of the ARDL procedure is then can show on the speed of adjustment when there is any shock in the determinant variables. The main findings from this study is the income, tourism price, real exchange rate, travelling costs and population are the main determinants for domestic and inbound tourism demand. It is interesting to note that tourist income is positively and tourism price is negatively related to domestic and inbound tourism demand in the long-run and short-run. Also, empirical results show for most developed and developing countries income and price are elastic (greater than one), therefore the tourism product is luxuries. These finding clearly supports the first and second parts of the hypothesis of present study. Moreover, from the finding, the domestic and inbound tourism expenditure did not have a positive effect on gross domestic product (GDP), but the capital investment and total export in the long-run had a bigger positive effect as compare to the tourism expenditure. So, this study highlights the reason for lower contribution of tourism expenditure to economic growth in Iraq in the long-run and short-run. This finding clearly supports the third part of the hypothesis of present study. Also, this study has found Iran is the largest source market of Iraq, because more than 90% of total arrival comes from Iran (especially after convention between Iraq and Iran in 1997 allowing coming Iranian tourist to Iraq) with shorter stay and lower spending. However, the Australia smaller source market of Iraq, because only 0.003% of total arrival from Australia visit to Iraq with longer stay and higher spending. Overall, the estimated models in this study are performed, since there are fulfill the diagnostic test. Thus, policy maker can use these results and finding for Implication and forecasting purpose.